Repertório contemporâneo de música de concerto e banda escolar cuiabana : reflexões e possíveis conexões - Santos, Jill Margarete Rodrigues Feitosa de Sousa (2022)
This dissertation aims to encourage reflections on possible connections between the repertoire of contemporary concert music and the universe of the school band, and as a consequence, it aims to awaken the interest of the members of school bands in Mato Grosso for different styles of repertoire through the introductory presentation, in a workshop format, on contemporary concert music and reflect on the possibilities of applying this repertoire to the school band. As secondary objectives, we investigate the philosophy behind the construction of band repertoires and how capitalistic subjectivity interferes at the time of this choice, as well as prior knowledge about the repertoire in question. The tools used for this study were the application of an introductory diagnostic questionnaire to investigate how the process of choosing the repertoire of bands from Cuiabá and MT works, a workshop on contemporary concert music and a final diagnostic questionnaire reflecting on the possibility of adapting this repertoire style for the formation of school band in the percussion category. The expected results, through the proposal presented, are to disseminate contemporary concert music, awakening interest in different musical styles for groups of bands, allowing access and knowledge to this contemporary music, thus breaking the paradigm of the mass media imposed by the capitalistic subjectivity of what must be appreciated today by the youth of Mato Grosso.